Implementasi Sistem Digital Brimen Pada Bri Unit Sleko-Madiun - Ade Nuria Finka Yuliana; Tika Panjawiyati; Meilinda Ike Wulandari; Sinta Dewi Oktaviasari; Elana Era Yusdita (JURNAL PUNDI, 2022)
The purpose of this study was to determine the filing and inputting procedures of BRIMEN and to conduct research on discrepancies between documents in the BRIMEN system and data stored in one place at Bank BRI Unit Sleko Madiun. The research method used is a quantitative method with data collection, namely observation and analysis of brimen data in BRI Unit Sleko. Good archiving procedures are needed, the goal is that existing documents are not lost and are easily found when needed. As an effort to manage customer documents properly, Bank BRI has created a digital system called Brimen (BRI Document Management System). The use of digital systems means making changes from conventional to digital systems in terms of services to fairly strict internal improvements. It can be concluded that there are seven stages in archiving Brimen starting from sorting brimen archives to arranging boxes on shelves. Meanwhile, Brimen input can be done in two ways, namely Brimen input from Microsoft Excel and BRIMEN registers (Manual List and Q-RIS).Keywords: Bank Rakyat Indonesia; Application of Digital Systems; Financial Institutions; Input Procedures; Brimen